1996
DOI: 10.1037/1082-989x.1.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Computing contrasts, effect sizes, and counternulls on other people's published data: General procedures for research consumers.

Abstract: We describe convenient statistical procedures that will enable research consumers (e.g., professional psychologists, graduate students, and researchers themselves) to reach beyond the published conclusions and make an independent assessment of the reported results. Appropriately conceived contrasts accompanied by effect size estimates often allow researchers to address precise predictions that the authors of the published report may have ignored or abandoned prematurely. We describe the use of t, F, and Z to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
409
0
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 634 publications
(426 citation statements)
references
References 49 publications
7
409
0
10
Order By: Relevance
“…Next, we assessed whether sex is a predictive variable for the mean STAXI-2 scores within each group (clinical-control) with an ANCOVA (adjusted by age and duration of the disorder for the PG sample). Pearson's correlation coefficients were calculated to examine the linear association between STAXI-2, SCL-90-R, and TCI-R direct scores, and absolute values above .30 were considered for practical significance (Rosnow & Rosenthal, 1996). Finally, the predictive capacity of the STAXI-2 scores (independent variables or predictors) on the intensity of the disorder (dependent variables or criteria) for the PG sample was evaluated thorough multiple linear regression models (for quantitative criteria, SOGS total score) and negative binomial models (for criteria that represent counting, such as number of the DSM-IV criteria and the total number of games briefed by the patient) adjusted by sex and duration of the disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we assessed whether sex is a predictive variable for the mean STAXI-2 scores within each group (clinical-control) with an ANCOVA (adjusted by age and duration of the disorder for the PG sample). Pearson's correlation coefficients were calculated to examine the linear association between STAXI-2, SCL-90-R, and TCI-R direct scores, and absolute values above .30 were considered for practical significance (Rosnow & Rosenthal, 1996). Finally, the predictive capacity of the STAXI-2 scores (independent variables or predictors) on the intensity of the disorder (dependent variables or criteria) for the PG sample was evaluated thorough multiple linear regression models (for quantitative criteria, SOGS total score) and negative binomial models (for criteria that represent counting, such as number of the DSM-IV criteria and the total number of games briefed by the patient) adjusted by sex and duration of the disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Effect sizes based on mean differences and standard deviations were calculated for studies that reported sufficient information (Rosnow and Rosenthal, 1996). For randomized studies, the effect size was the difference between the treatment mean and the attention control mean divided by an estimate of standard deviation pooled from both groups.…”
Section: Methodsmentioning
confidence: 99%
“…This conservative approach (Rosenthal, 1991) allows a better representation of the existing literature and was used only when it was possible to determine the direction of the effect through the provided descriptive statistics (15.22% of cases; for a similar procedure, see Bar-Haim et al, 2007). In cases in which the contrast of interest was not directly tested through a planned test (e.g., positive vs. neutral), but through a main effect test that included other modalities (e.g., main effect of valence: Positive, negative, or neutral), the effect size for the contrast of interest (i.e., positive vs. neutral) was extracted through the maximum possible contrast F method (MPC-F; Rosnow & Rosenthal, 1996). The method used to extract the effect size (i.e., F, t, p, and MPC-F) was entered as a control moderator and the between-groups homogeneity statistic revealed a significant effect (Q B ϭ 10.819, p ϭ .012).…”
Section: Methods Inclusion Criteriamentioning
confidence: 99%